Structural Dynamics of Lateral and Diagonal Loops of Human Telomeric G-Quadruplexes in Extended MD Simulations - Islam, Barira; Stadlbauer, Petr; Krepl, Miroslav; Havrila, Marek; Haider, Shozeb; Sponer, Jiri (Journal of chemical theory and computation, 2018)
The NMR solution structures of human telomeric (Htel) G-quadruplexes (GQs) are characterized by the presence of two lateral loops complemented by either diagonal or propeller loops. Bases of a given loop can establish interactions within the loop as well as with other loops and the flanking bases. This can lead to a formation of base alignments above and below the GQ stems. These base alignments are known to affect the loop structures and relative stabilities of different Htel GQ folds. We have carried out a total of 217 μs of classical (unbiased) molecular dynamics (MD) simulations starting from the available solution structures of Htel GQs to characterize structural dynamics of the lateral and diagonal loops, using several recent AMBER DNA force-field variants. As the loops are involved in diverse stacking and H-bonding interactions, their dynamics is slow, and extended sampling is required to capture different conformations. Nevertheless, although the simulations are far from being quantitatively converged, the data suggest that multiple 10 μs-scale simulations can provide a quite good assessment of the loop conformational space as described by the force field. The simulations indicate that the lateral loops may sample multiple coexisting conformations, which should be considered when comparing simulations with the NMR models as the latter include ensemble averaging. The adenine-thymine Watson-Crick arrangement was the most stable base pairing in the simulations. Adenine-adenine and thymine-thymine base pairs were also sampled but were less stable. The data suggest that the description of lateral and diagonal GQ loops in contemporary MD simulations is considerably more realistic than the description of propeller loops, though definitely not flawless.
Keywords: simulace molekulární dynamiky; vodíková vazba; Telomere; telomery; párování bází; G-kvadruplexy; Base Pairing; G-Quadruplexes; Humans; Molecular Dynamics Simulation; Hydrogen Bonding; DNA; lidé